St. Paul : The Unmade Movie - Mariniello, Silvestra (Cinémas)

(untitled) (Cinémas, 1999)
ABSTRACTThis essay addresses the notion of "screenplay" elaborated by the film director Pier Paolo Pasolini, in his essay "The Screenplay as a 'Structure That Wants to be Another Structure'," with reference to his Project for a Film of St. Paul. Pasolini's St. Paul, which would have transposed the story of the apostle into our own day, by situating it in New York (Rome), Paris (Jerusalem), present day Rome (Athens), and London (Alexandria), never made it to film. The project, however, gives the whole of Pasolini's cinematographic poetic in condensed form; it is a text which inhabits, in a critical and self-conscious way, the space between writing and film which is proper to the screenplay. The aim of this essay is to show the movement, the play of allusions and references, that form the very basis of the cinematographic screenplay.